2022
DOI: 10.2147/ijgm.s366170
|View full text |Cite
|
Sign up to set email alerts
|

Serum NOX4 as a Promising Prognostic Biomarker in Association with 90-Day Outcome of Severe Traumatic Brain Injury

Abstract: Purpose Nicotinamide adenine dinucleotide phosphate oxidase 4 (NOX4) is related to brain oxidative stress. We attempted to examine the association between serum NOX4 levels, severity and prognosis of severe traumatic brain injury (sTBI). Methods We measured serum NOX4 levels in 105 patients with sTBI. Trauma severity was assessed using Glasgow coma scale (GCS) and Rotterdam computed tomography (CT) classification. Study outcome data on death and worst outcome (Glasgow o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…We investigated the associations of serum CKLF1 levels with trauma severity and prognosis through a linear regression model, a binary logistic regression model, and a Cox proportional hazard model and found that serum CKLF1 levels were independently correlated with GCS scores and Rotterdam CT classification and were independently associated with 180‐day mortality and poor prognosis in sTBI patients. In current clinical studies, GCS scores and Rotterdam CT classification are often used to assess trauma severity and predict the prognosis of patients (Jiang et al., 2022 ; Yang et al., 2021 ; Zhang et al., 2023 ). We therefore hypothesized that serum CKLF1 levels may be strongly associated with trauma severity, 180‐day mortality, and the long‐term function prognosis of sTBI.…”
Section: Discussionmentioning
confidence: 99%
“…We investigated the associations of serum CKLF1 levels with trauma severity and prognosis through a linear regression model, a binary logistic regression model, and a Cox proportional hazard model and found that serum CKLF1 levels were independently correlated with GCS scores and Rotterdam CT classification and were independently associated with 180‐day mortality and poor prognosis in sTBI patients. In current clinical studies, GCS scores and Rotterdam CT classification are often used to assess trauma severity and predict the prognosis of patients (Jiang et al., 2022 ; Yang et al., 2021 ; Zhang et al., 2023 ). We therefore hypothesized that serum CKLF1 levels may be strongly associated with trauma severity, 180‐day mortality, and the long‐term function prognosis of sTBI.…”
Section: Discussionmentioning
confidence: 99%